Transcription Factors Interplay Orchestrates the Immune-Metabolic Response of Leishmania Infected Macrophages - Bichiou, Haifa; Bouabid, Cyrine; Rabhi, Imen; Guizani-Tabbane, Lamia (Frontiers in Cellular and Infection Microbiology, 2021)
Leishmaniasis is a group of heterogenous diseases considered as an important public health problem in several countries. This neglected disease is caused by over 20 parasite species of the protozoa belonging to the Leishmania genus and is spread by the bite of a female phlebotomine sandfly. Depending on the parasite specie and the immune status of the patient, leishmaniasis can present a wide spectrum of clinical manifestations. As an obligate intracellular parasite, Leishmania colonize phagocytic cells, mainly the macrophages that orchestrate the host immune response and determine the fate of the infection. Once inside macrophages, Leishmania triggers different signaling pathways that regulate the immune and metabolic response of the host cells. Various transcription factors regulate such immune-metabolic responses and the associated leishmanicidal and inflammatory reaction against the invading parasite. In this review, we will highlight the most important transcription factors involved in these responses, their interactions and their impact on the establishment and the progression of the immune response along with their effect on the physiopathology of the disease.